DAKWAH SIMBOLIK HIJRAH DAN MODERASI ISLAM DI MEDIA ONLINE - Muhamad Fahrudin Yusuf (Aqlam: Journal of Islam and Plurality, 2019)
Abstract "Hijrah" with all its symbolic identities today is one of the most contemporary Islamic issues. This research aims to describe and analyze the meaning of "hijrah" ideologically. This research focuses on the discourse of "hijrah" through the representation of the news of "hijrah" photos of the artists and the supplementary news in online media such as "Kapanlagi.com" and "kiblat.net". The method used in this research is discourse analysis. Technique of analyzing the data used in this research is semiotic analysis. The result of data analysis showed that the meaning of "hijrah" is still symbolic, namely professional change, the change of name and performance. In addition, online media have not fully supported the Islamic moderation movement.Key Word: Hijrah, Meaning, Ideology, Islamic Moderation. Abstrak “Hijrah” dengan segala identitas simboliknya dewasa ini menjadi salah satu isu Islam kontemporer terhangat menghiasi ruang media. Untuk tujuan mendeskripsikan dan menganalisis makna “hijrah” secara ideologis, penelitian ini memfokuskan diri wacana “hijrah” melalui representasi pada berita foto “hijrah” artis dan berita pelengkapnya yang ada di media online “kapanlagi.com” dan “kiblat.net”. Menggunakan analisis wacana sebagai metode penelitian dan analisis semiotika sebagai metode analisis data, didapati hasil bahwa makna “hijrah” menurut media online masih bersifat simbolik, yaitu perubahan profesi, perubahan nama dan penampilan. Artinya, media online belum sepenuhnya mendukung gerakan moderasi Islam.Kata kunci: Hijrah, Makna Simbolik, Ideologi, Moderasi Islam.